Parasitic‐coupled high‐gain graphene antenna employed on PBG dielectric grating substrate for THz applications. Issue 1 (12th September 2019) - Kushwaha, Ritesh Kumar; Karuppanan, P.
Abstract: In THz frequency region, the high‐gain miniaturized patch antenna is essential to overcome the atmospheric losses. A novel dual‐band miniaturized graphene antenna array with parasitic‐coupled feed and mounted on PBG dielectric grating substrate is proposed in the operating frequency band from 0.85 to 1.04 THz. The analysis of graphene surface conductivity, surface wave polariton (SPP) of photonic band gap (PBG) substrate, and the dielectric grating substrate has been done for the verification of a projected design. Parametric analysis of PBG radius, periodic perturbation of dielectric grating substrate, and mutual coupling distance has been verified to achieve the enhanced radiation characteristics of the antenna. The minimum return loss of −52.58 dB, VSWR of 1.005, impedance bandwidth of 33.34 GHz, the peak gain of 16.4 dB, and peak directivity of 17 dBi has been observed for the projected design. The parasitic‐coupled method is suitable to reduce the complexity of the antenna array and proposed design is useful in imaging, security using spectroscopy, and wireless communication applications.